UNIVERSITY AS AN INNOVATIVE PRODUCTION UNIT TO OVERCOME THE NEGATIVE CONSEQUENCES OF SANCTION PRESSURE - Prozorov, A. S. (Social’no-ekonomiceskoe upravlenie teoria i praktika, 2023)
This article describes the actual problem and the need to develop a methodology/algorithm for working with innovative projects in universities in the face of sanctions pressure. The article discusses both theoretical and practical aspects of this problem, and puts forward the idea that universities can act as innovative production units to overcome the negative consequences of sanctions pressure. The implementation of this idea is ensured by creating the necessary favorable organizational, financial, infrastructural and other conditions conducive to the creation and implementation of innovative projects in universities. The role of universities in the innovation ecosystem is considered, including taking into account world experience. The article is based on the latest scientific research in the field of innovation management and proposes to develop a methodology/algorithm for working with innovative projects in universities, from the idea generation stage to successful implementation. It considers issues related to the selection of an innovative project, its financing, planning and management, as well as the interaction between the project team and potential partners and investors. The development of such a methodology can help in the process of generating ideas and successfully implementing innovative projects in universities, which in turn contributes to sustainable economic development.